An Autopsy Based Study about Epidemiological Profile of Deaths Due To Hanging in Central India Region, Madhya Pradesh - Kumar Vishwakarma, Ashish; Thakur, P S; Singh, B K; Singh, B K; Pandey Jain, Ankit; Pendro, T S; Soni , S K (Journal of Indian Academy of Forensic Medicine, 2021)
This is a 1 year autopsy based prospective study carried out on cases of death due to hanging in mortuary of Department of Forensic Medicine & Toxicology, Mahatma Gandhi memorial Medical College and M.Y. Hospital, Indore, (M.P.) between February 2019 and January 2020. In our study, 172 cases (134 males & 38 females) of death due to hanging brought for medico legal post mortem examination were taken. The most common age for hanging is found to be between 21-30 years in 36.63% cases. Hindus constituted 93.02% of total study population. 57.56% were married and 42.44% cases were unmarried. Hanging deaths occurring in urban areas (83.14%) outnumbered that of rural area (16.86%). 45.35% cases had completed their secondary education. 61.04% incidences happened in nuclear families. Students (30.81% cases) and self employed persons (30.81% cases) constituted more than half of total cases. Majority of victims (72.09% cases) in this study belonged to the middle class socio-economic group, with 19.77% brought in on Wednesday followed by Sunday in 16.86% cases. In our study, majority of victims were found at night time (in 36.63% cases) followed by early morning (in 25.0% cases). 95.93% cases were found hanging at indoor locations.